The Effect of Firm Age, Profitability, Audit Opinion, and Solvency on Audit Report Lag Empirical Studies: Non Financial and Banking Sector Companies - Indri Kusumaningrum, Fitria; Astuti, Sri; Sutoyo, Sutoyo (Journal of International Conference Proceedings, 2022)
This study means to inspect and get observational proof in regards with the impact of firm age, benefit, review assessment, and dissolvability on review report slack.The number of days between the end of the company's fiscal year and the audit date stated in the independent auditor's report is used to measure audit report lag.Profitability is measured using the Return On Assets (ROA) formula, audit opinion is measured using a dummy variable, and solvency is measured using the Debt to Asset Ratio (DAR) formula. Company age is selected between the year of research and the year the company was founded.During the COVID-19 pandemic, companies in the non-financial and banking sectors that were listed on the Indonesia Stock Exchange (IDX) were used as the population.Purposive sampling is combined with non-probability sampling in the sampling technique.There were 876 observations in total for this study.This study employs multiple linear regression analysis as the analytical model.Audit report lag in non-financial and banking sector companies listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic in 2019-2020 does not appear to be influenced by audit opinion or solvency, according to the findings of this study. Keywords: Firm Age, Profitability, Audit Opinion, Solvency, Audit Report Lag